Statistics: are we related?. (4th March 2013) - Scott, M.; Flaherty, D.; Currall, J.
<x xml:space="preserve">Abstract</x> This short addition to our series on clinical statistics concerns relationships, and answering questions such as "are blood pressure and weight related?" In a later article, we will answer the more interesting question about how they might be related. This article follows on logically from the previous one dealing with categorical data, the major difference being here that we will consider two continuous variables, which naturally leads to the use of a Pearson correlation or occasionally to a Spearman rank correlation coefficient.